Selective Oxidative Dehydrogenation of Ethane and Propane over Copper‐Containing Mordenite: Insights into Reaction Mechanism and Product Protection - Artsiusheuski, Mikalai A.; Verel, René; van Bokhoven, Jeroen A.; Sushkevich, Vitaly L. (Angewandte Chemie International Edition, 2023)
Copper(II)‐containing mordenite (CuMOR) is capable of activation of C−H bonds in C 1 ‐C 3 alkanes, albeit there are remarkable differences between the functionalization of ethane and propane compared to methane. The reaction of ethane and propane with CuMOR results in the formation of ethylene and propylene, while the reaction of methane predominantly yields methanol and dimethyl ether. By combining in situ FTIR and MAS NMR spectroscopies as well as time‐resolved Cu K‐edge X‐ray absorption spectroscopy, the reaction mechanism was derived, which differs significantly for each alkane. The formation of ethylene and propylene proceeds via oxidative dehydrogenation of the corresponding alkanes with selectivity above 95 % for ethane and above 85 % for propane. The formation of stable π‐complexes of olefins with Cu I sites, formed upon reduction of Cu II ‐oxo species, protects olefins from further oxidation and/or oligomerization. This is different from methane, the activation of which proceeds via oxidative hydroxylation leading to the formation of surface methoxy species bonded to the zeolite framework. Our findings constitute one of the major steps in the direct conversion of alkanes to important commodities and open a novel research direction aiming at the selective synthesis of olefins.